Physiological differences between professional and elite road cyclists - Lucia, A.; Pardo, J.; Durantez, A.; Hoyos, J.; Chicharro, J. L. (International Journal of Sports Medicine, 1998)
The purpose of this study was to compare the physiological responses of professional and elite road cyclists during an incremental cycle ergometer test. Twenty-five elite cyclists (EC; 23+/-1 yr) and 25 professional cyclists (PC; 25+/-2yr) performed a ramp protocol (increases of 25 W x min(-1)) during which the following parameters were measured: oxygen consumption (VO2), pulmonary ventilation (VE), ventilatory equivalents for oxygen and carbon dioxide (VE x VO2(-1) and VE x VCO2(-1), respectively), respiratory exchange ratio (RER), ventilatory thresholds 1 and 2 (VT1 and VT2, respectively), blood lactate, and electromyographic activity (EMG) of the vastus lateralis. Significant differences existed between the two groups mainly at submaximal intensities, since both VT1 and VT2 occurred at a higher exercise intensity (p<0.001) in PC than in EC (VT2: 80.4+/-6.6 vs 87.0+/- 5.9% VO2max in EC and PC, respectively). Lactate levels showed a similar response in both groups at low-to-moderate intensities (< 300 W), and thereafter blood lactate was significantly higher in EC. Finally, the "electromyographic threshold" (EMGT) occurred at a significantly higher intensity (p < 0.05) in PC when compared to EC (64.7+/-14.2 vs 56.0+/-14.9% VO2max, respectively). It was concluded that, in comparison with EC, PC exhibit some remarkable physiological characteristics such as a high VT2, an important reliance on fat metabolism even at high power outputs, and several neuromuscular adaptations.